Blood Pressure Response in Miners Exposed to Chronic Intermittent Hypoxia in Chile - Lang, Morin; Paéz, Valeria; Maj, Giacomo; Silva-Urra, Juan; Labarca-Valenzuela, Cristián; Caravita, Sergio; Faini, Andrea; Cantuarias, Javier; Perez, Oscar; Bilo, Grzegorz; Parati, Gianfranco (Frontiers in Cardiovascular Medicine, 2021)
Limited information is available on blood pressure (BP) behavior in workers exposed to chronic intermittent hypoxia (CIH), and even less is known regarding its effects on 24-hour ambulatory BP in those affected by arterial hypertension at sea level (SL). The aims of this study were to assess clinic and 24-hour ambulatory BP at SL and at high altitude (HA, 3870 meters above sea level) in workers exposed to CIH, and to compare BP response to HA exposure between normotensive and hypertensive workers. Methods. 19 normotensive and 18 pharmacologically treated hypertensive miners acclimatized to CIH were included, whose work was organized according to a “7 days-on-7 days-off” shift pattern between SL and HA. All measurements were performed on the 2nd and 7th day of their HA shift and after the 2nd day of SL sojourn. Results. Compared to SL, 24h systolic (SBP) and diastolic BP (DBP) increased at HA (+14.7±12.6 mmHg p<0.001 and +8.7±7.2 mmHg p<0.001, respectively), and SBP nocturnal fall decreased consistently (-4.1±9.8mmHg p<0.05) in all participants, with hypertensives showing higher nocturnal DBP than normotensives (p<0.05) despite the current therapy. Also, heart rate (HR) nocturnal fall tended to be reduced at HA. In addition, the 24h SBP/DBP hypertension threshold of ≥130/80-mmHg was exceeded by 39% of workers at SL and by 89% at HA. Clinic HR, SBP and DBP were significantly higher on the 2nd day of work at HA compared with SL, the increase being more pronounced for SBP in hypertensives (p<0.05) and accompanied by, on average, mild altitude sickness in both groups. These symptoms and the values of all cardiovascular variables decreased on the 7th day at HA (p<0.05) regardless of CIH exposure duration. Conclusion. Long history of work at HA according to scheduled CIH did not prevent the occurrence of acute cardiovascular changes at HA during the first days of exposure. The BP response to HA tended to be more pronounced in hypertensive than in normotensive workers, despite being already treated, the BP changes being more evident for 24h ambulatory BP. 24h ABPM is a useful tool for an appropriate evaluation of BP in CIH workers.